Development of Socio-Scientific Issues (SSI) Based Digital Teaching Materials with A Flipped Classroom Model to Increase Students' Interest and Cognitive Learning Outcomes - Ahmad Azan Akbari; Akhlis, Isa; Masfuah, Siti (Universitas Negeri Semarang, 2025)
This study aims to develop Socio-Scientific Issues (SSI)- based digital teaching materials on impulse and momentum, and to determine whether they are suitable and effective in enhancing students' interest and learning outcomes. The research employed the Research and Development (R&D) method, utilizing the ADDIE development model, which comprises the stages of analysis, design, development, implementation, and evaluation. Data collection techniques include observation, interviews, learning interest questionnaires, and learning outcomes tests. The data were analyzed through a feasibility test and an effectiveness test. The results showed that SSI-based digital teaching materials were feasible to use and had a positive effect on increasing students' interest and cognitive learning outcomes. This research offers benefits by providing alternative teaching materials that are contextual, interesting, and relevant, thereby improving the quality of physics learning in schools.